An Efficient Organic Additive to Control the Crystallization Rate of Aliphatic Polyketone： A Non-isothermal Crystallization Kinetics Study - Zhang, He-xin; Park, Min-Jeong; Moon, Young-Kwon; Ko, Eun-Bin; Zhang, Xue-quan; Yoon, Keun-Byoung (Chinese journal of polymer science, 2017)
Three types of organic compounds--two carboxylic acids and an anhydride, were used as additives for polyketone （PK）. The effect of the additive structure and their feed ratios on the melting temperature, crystallization temperature, and crystallization rate of PK were studied. We found that the crystallization temperature could be reduced significantly by introducing a small quantity of organic additive, in particular, an anhydride. On addition of 1 phr of anhydride, the crystallization temperature was reduced by 10.7 ℃. Therefore, the non-isothermal crystallization kinetics of aliphatic PKJanhydride blends with various feed ratios was investigated using DSC. The results were analyzed by various theoretical models, such as Avrami, Ozawa and combined Avrami-Ozawa models.